(untitled) - Cipolla, Carlo M. (New York, 1976)
During the seven hundred years before the Industrial Revolution, the stage was set for Europe's transformation from a backward agrarian society to a powerful industrialized society. An economic historian of international reputation, Carlo M. Cipolla explores the process that made this transformation possible. In so doing, he sheds light not only on the economic factors but on the culture surrounding them.The Third Edition includes substantial revisions and new material throughout the book that will secure its standing as the most useful history available of preindustrial Europe.
Keywords: Châu Âu,Europe; Điều kiện kinh tế,Economic conditions